Training of traffic police officers in the use of physical force in situations of operational service activities - Bakulin N.P.; Kvasov V.B. (Theory and Practice of Physical Culture, 2025)
Introduction. Physical training of employees of internal affairs bodies is aimed at developing professionally significant physical qualities, developing combat fighting skills and the ability to use physical force in situations of operational and service activities. [1]. Currently, the current direction of physical training of the traffic police officers of the Ministry of Internal Affairs of Russia is training in the use of combat techniques in situations of operational and service activities. Purpose of the research – identifying current methods of training traffic police officers in the situational use of physical force. Research methodology and organization. The study was organized and conducted at the Tyumen Institute for Advanced Training of the Ministry of Internal Affairs employees in the period from 2019 to 2024. The following scientific methods were used in the study: analysis of the practice of using physical force by police officers, studies and scientific literature; modeling the educational process of advanced training; systematization of educational content. Results and its discussion. As a result of the study, the training topic “Features of the use of physical force in typical situations of operational and service activities of employees of the State Traffic Safety Inspectorate of the Ministry of Internal Affairs of Russia” was developed and tested. [2]. This topic is structurally included in the thematic plan of the optional discipline “Current issues of the activities of the traffic police units of the Ministry of Internal Affairs of Russia” of the professional training program for persons for the position of “Police officer”. Within the framework of this training topic, students are taught the techniques and tactics of using combat fighting techniques in situations of operational and official activities of traffic police officers of the State Traffic Safety Inspectorate of the Ministry of Internal Affairs of Russia. Current issues include situations where physical force is used to remove an offender from a vehicle; protection from blows with piercing and cutting objects in the confined space of a vehicle; protection from attacks on police officers when checking the vehicle owner’s identity documents. Conclusion. As a result of the study, the training topic “Features of the use of physical force and special means in typical situations of operational and official activities of employees of the State Traffic Safety Inspectorate of the Ministry of Internal Affairs of Russia” was developed and tested within the framework of the training of students in the professional training programs for persons in the position of “Policeman”. As a result of the implementation of the training topic, the effectiveness of the use of physical force in the situations under consideration increased by 26%. The results of the study confirm the effectiveness of the developed training topic.